1990
DOI: 10.1287/mnsc.36.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Programming Approach to a Class of Nonpoint Source Pollution Control Problems

Abstract: This paper presents a new approach to modeling, analyzing, and solving a class of environmental control problems dealing with sediment deposition. An efficient dynamic programming algorithm is designed to handle the spatial characteristics of soil movement through a watershed, and its ultimate impact on water channels and/or reservoirs. The model generates "sediment abatement cost frontiers" which summarize the trade-off information needed for watershed planning and management. This information can also be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Bloemhof-Ruwaard et al (1995) observed the earliest studies on the application of operational research (OR) optimization models to environmental management (e.g., Böttcher and Rembold, 1977;Das and Haimes, 1979;Batta and Chiu, 1988;Ellis, 1988;Bouzaher et al, 1990). Brandenburg et al (2014) observed that, among the extant research related to the SCM perspective, sustainability is often externally motivated by the government, the customers or stakeholders (e.g., Gold et al 2010;Seuring and Müller, 2008), and a vertical coordination for improving environmental performance among supply chain firms is required (Carter and Rogers, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bloemhof-Ruwaard et al (1995) observed the earliest studies on the application of operational research (OR) optimization models to environmental management (e.g., Böttcher and Rembold, 1977;Das and Haimes, 1979;Batta and Chiu, 1988;Ellis, 1988;Bouzaher et al, 1990). Brandenburg et al (2014) observed that, among the extant research related to the SCM perspective, sustainability is often externally motivated by the government, the customers or stakeholders (e.g., Gold et al 2010;Seuring and Müller, 2008), and a vertical coordination for improving environmental performance among supply chain firms is required (Carter and Rogers, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Integrated modeling systems range from farm-level (Foltz et al 1993;Taylor et al 1992;Wossink et al 1992), to watershed (Bouzaher et al 1990;Lakshminarayan et al 1991), and ultimately to regional (Bernardo et al 1993;Bouzaher et al 1995;Lakshminarayan et al 1996) applications. In each of these systems, functions and/or models are incorporated to predict environmental indicators for different combinations of landscape, soil, management, and climate conditions.…”
Section: Validation Of Epic For Two Watersheds In Southwest Iowamentioning
confidence: 99%
“…12 (Jorgenson, 2009) Operations research tools to help EPA counter drinking water contamination threats (Murray et al, 2009) Determinants of organic pollution in poor nations (Shandra et al, 2008) Fertilizer runoff into nearby river from new housing development (Woolsey, 2008) FDI on water and air (Jorgenson, 2007) Secondary transmissions of infection in drinking water systems (Chick et al, 2003) Historical view of how chemical companies, pollution experts, and government agencies defined problems of water pollution (J. K. Smith, 2000) Measures to minimize water pollution from a pig slaughterhouse (Stoop, 1999) Forecast lake algal dynamics (van Straten & Keesman, 1991) Forecast structural changes to understand bulking sludge in biological treatment of wastewater (Seixas et al, 1991) Carbon, phosphorous cycles from anthropogenic influences (Beck & Halfon, 1991) Soil movement impact on water channels and reservoirs (Bouzaher et al, 1990) Water pollution control of the Huangpu River in the Peoples' Republic of China (Pollock & Chen, 1986) Water treatment for stream-dissolved oxygen (Ecker, 1975) Saltwater intrusion Management of river salinity (Jakeman et al, 1991) Economic Costs to treat water to eliminate pollution FDI impact on water pollution (Jorgenson, 2009) Large-scale study (4,000 surveys over 4 years) of reference dependence on people's choices between areas that differ on cost of living and quality of the lakes and rivers to determine valuation of a nonmarket good (Huber et al, 2008) China environmental risks overwhelm opportunities? (Economy & Lieberthal, 2007) Increase profits by...…”
Section: Results: a Water Taxonomymentioning
confidence: 99%